Exploring the Employability and Relevancy of Arabic Graduates in Southwest Nigeria - Toyyib Abiodun Mustapha; Abdul Shakour Duncan Preece; Ismail Hussein Amzat (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Abstract This qualitative study explores the employability and relevancy of Arabic graduates in southwest Nigeria. The study helps to analyse the definition of the employability and relevance of Arabic graduates in the Southwest among the Arabic graduates. The study’s central phenomenon is to explore employability skills needed for Arabic graduates in Nigeria. The study used a phenomenology study to achieve the research objectives and answer the research questions. A semi-structured interview was used in the study, while 11 participants were interviewed. Inductive analysis was used to analyse the interview transcript. Furthermore, the findings show that employers need employability skills such as soft skills. The result indicates that Arabic graduates lack communication skills, networking, personal competence, and information technology. Thus, the findings cannot be generalised because only a few participants were interviewed. The study also recommends that the policymakers include the English language and graduate employability skills as compulsory courses in the Arabic curriculum to enhance the graduates’ speaking skills and employability skills since Nigeria is not an Arabic-speaking country.